Implementasi SDGs Pada Anak Usia Sekolah Dasar Melalui BerLiMPah (Bersama Lima Menit Pungut Sampah) - Unggul, Latifa Destami; Rahim, Meiliza Erfa; Fazira, Nadia Kinanti; Sholihah, Nadiyatush; Rizkiana, Nila (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
This article discusses the implementation of SDGs in community service research, especially education on the grouping of waste types in State Elementary School 38 Mataram as a first step to increase students' awareness of the importance of sorting types of waste. Based on observations made, it was found that there has been no concrete action on grouping organic and inorganic waste in State Elementary School 38 Mataram. Therefore, students of the mathematics education study program at Mataram University who are registered as participants in the teaching campus of batch 6 placement of State Elementary School 38 Mataram initiated the